Metabolic scaling variation as a constitutive adaptation to tide level in Mytilus galloprovincialis - Pérez-Cebrecos, Maitane; Berrojalbiz, Xabier; Izagirre, Urtzi; Ibarrola, Irrintzi (Frontiers in Marine Science, 2023)
Understanding how allometric exponents vary in the different biologically determined patterns turns out to be fundamental for the development of a unifying hypothesis that intends to explain most of the variation among taxa and physiological states. The aims of this study were (i) to analyze the scaling exponents of oxygen consumption at different metabolic rates in Mytilus galloprovincialis according to different seasons, habitat, and acclimation to laboratory conditions and (ii) to examine the variation in shell morphology depending on habitat or seasonal environmental hazards. Intertidal mussels showed lower allometric exponents and metabolic levels than subtidal mussels, a response that did not change for at least two months after the environmental signal was removed. We suggest that this is the result of intertidal mussels investing fundamentally in surface-dependent organs (gill and shell), with the exception of the higher values obtained in May as a likely consequence of gonadal tissue development. Subtidal mussels, on the contrary, are probably in constant demand for volume-related resources, which makes them consistently obtain an allometric exponent of around 0.87.